1983
DOI: 10.3354/meps012077
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relationships between phytoplankton, bacteria and heterotrophic microflagellates in shelf waters

Abstract: Estimates of the numbers and biomass of bacteria as a function of depth in coastal and upwelling waters off the western approaches to the Engllsh Channel and in the southern Benguela upwelling region off the Cape Peninsula, South Africa, show that the numbers of bacteria are correlated with the standing stocks of phytoplankton as assessed by chlorophyll a concentration. Standing stocks of heterotrophic microflagellates in the size range 3 to 10 pm, amount to some 16.9 % on average, of bacterial standing stocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
1
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 19 publications
9
55
1
1
Order By: Relevance
“…Cole et al (1988) summarized 70 foreign datasets and found a mean slope of 0.52. Ducklow and Carlson (1992) listed in their overview several slopes, half of them significant, and reported a range of 0.5-0.8, a part from a study from the Antarctic Weddel Sea (Cota et al 1990;slope=0.11) and another from the Benguela upwelling (Linley et al 1983;slope=1.05). Except for these two unusual values, the slopes of our study in the Wadden Sea are always smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Cole et al (1988) summarized 70 foreign datasets and found a mean slope of 0.52. Ducklow and Carlson (1992) listed in their overview several slopes, half of them significant, and reported a range of 0.5-0.8, a part from a study from the Antarctic Weddel Sea (Cota et al 1990;slope=0.11) and another from the Benguela upwelling (Linley et al 1983;slope=1.05). Except for these two unusual values, the slopes of our study in the Wadden Sea are always smaller.…”
Section: Discussionmentioning
confidence: 99%
“…As another approach to the assessment of bacterial carbon conversion efficiency, a few authors have attempted to set up carbon balances for bacterioplankton populations. Newel1 and coworkers (Newel1 et al 1981, Linley et al 1983, Linley & Newel1 1984) studied degradation of plant detritus in mixed cultures of marine bacteria. Bacterial carbon yield was estimated from direct counts (Hobbie et al 1977) and compared to loss of carbon substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological significance of nanoflagellates as consumers of the picoplankton has been suggested by studies describing the ubiquity of picoplankton and their nanoflagellate grazers in the marine environment (Sieburth 1976, Sieburth et al 1978, Johnson & Sieburth 1979, 1982, Burney et al 1981, 1982, Caron et al 1982, Fenchel 1982c, Azam et al 1983, Linley et al 1983, Davis et al 1985. Current methods to estimate the grazing potential of nanoplankters include the use of radioisotopes (Haney 1973, Holhbaugh et al 1980, Lessard & Swift 1985, the correlation of the abundance of predators and prey , the difference between potential and observed bacterial growth rates (Davis & Sieburth 1984), or the comparison of prey densities with and without predators (Peterson et al 1978, Fuhrman & McManus 1984, Wright & Coffin 1984.…”
Section: Introductionmentioning
confidence: 99%